Border Oasis: Water and the Political Ecology of the Colorado River Delta - Taylor Hansen, Lawrence Douglas (Frontera Norte, 2017)
1940-1975, Evan R. Ward, Tucson, Arizona, University of Arizona Press, 2003, 208 pp.